From fish physiology to ecosystems management: Keys for moving through biological levels of organization in detecting environmental changes and anticipate their consequences. (July 2018) - Pérez-Ruzafa, Angel; Pérez-Marcos, María; Marcos, Concepción
Graphical abstract: Highlights: Bioindicators to detect environmental stress are used from cell to ecosystem scale. Scaling from physiological indicators to ecosystem consequences is a challenge. Biological traits show regularities relating individual with population responses. These relationships are flexible throughout ontogeny and the life of individuals. The allocation of energy budget links physiological and community indicators. Abstract: Tackling environmental problems not only requires the detection of harmful agents or the drivers that induce changes in ecosystems and their effects, but also knowledge of their action mechanisms and the processes involved in order to design solutions, recover the damaged systems and, above all, prevent any deterioration before it occurs. In recent years conservation physiology has been proposed as a discipline that could play an important role in this context. However, the main problem in generalizing physiological indicators in order to assess ecological status is the leap in scale from the internal physiology of an individual to its relevance for ecosystem functioning. In this paper, we propose that the study of the physiological bases and epigenetic mechanisms that determine the allocation of energy resources, in the context of Dynamic Energy Budget theory, can be the hinge that allows us to pass from the physiology of the individual to the scale of population dynamics, the structure of populations and ecosystems. This proposal is based on the strong relationship shown by the parameters of the life story of individuals, such as body growth rate, maximum size, life expectancy or generation time, with the parameters that determine population growth and the ecological strategies of the species. There is growing evidence that the relationship between these parameters is not completely fixed and does not only respond to evolutionary scales, but may be flexible within certain limits throughout ontogeny and the life of individuals, producing consequences in populations in response to environmental conditions, environmental stress and, in the case of fish, the effects of fishing. Lay summary: Biological index to detect environmental impacts can be applied from cell to ecosystem scale. However, at lower levels, although they give important information on the mechanisms involved it is difficult to infer the real consequences of the detected changes on the ecosystems. The review of the regularities existing in ecological guilds relationships of fishes suggests that the study of the physiological and epigenetic bases that determine the allocation of energy resources in the context of Dynamic Energy Budget theory can be the hinge that allows us to pass from the effects on the physiology of the individual to the scale of population dynamics and ecosystems when modelling the consequences of changes in environmental stress.